Design and fabrication of power window apparatus (frame type) - Mohd Hizir Arafat, Tambun (2007)
This Power window apparatus project main purpose is to train final year student for hands on experience and to work by their self. The study of manufacturing is very important to ensure student understand the requirements to do in this project. This project is about designing and fabricating the Power Window Apparatus for experimental use to help the students in a Automotive class for easy understand if the basic system of power window and how it works. This project involves the process of designing the test panel by considering the shape and also the advantages for student to use in their learning process. After the design has completed, it was transformed to the real product by fabricating process. This project also required analysis to test the power window operation failure factor. Numerous methods and process involve in this project for instance joining using welding process. After all the process have been done, this power window apparatus help us to understand the fabrication and designing process that involved in this project.